Pengaruh Pembacaan Râtib Al-Haddâd di Ponpes Al-Munawwarah: Tinjauan Living Qur’an terhadap Kegiatan Keputrian - Ridwan Hasbi; Ira Riswana; M. Ridwan Hasbi; Jani Arni (AL-FIKRA, 2023)
Al-Munawwarah Islamic boarding school has many methodsto form of character for the santri, from discipline to the practice of zikir of Ratib al-Haddad. Character building is a very urgent part of being a santri so that all means leading towards it are carried out. Among these facilities was the reading of Ratib al-Haddad in jamaah every day except Tuesday night and Friday night after Maghrib prayer led by one of the teachers. This research is focused on the practice of zikir of Ratib al-Haddad in the santriwati (female student) environment in forming characters with the zikir consisting of surah / verses of the Quran and kalimah thayyibah so that they can influence the personality of santriwati. This research aims to examine the effect of the practice of reading specifically the surah / verse of the Quran which has its own fadhilah in the mufassir's view. The method used in this research is a Qualitative Descriptive analysis that reveals field practice with its contextualized impact on living Quran. This living Quran research is formulated in a surah or verse in Ratib al-Haddad which has its own virtues such as a cure for all diseases, protection from various disorders and dangers. Examination of the influence of recitation of the zikir of Râtib al-Haddâd for santriwati's life includes two categories, namely its influence in personal life such as increasing enthusiasm in learning, discipline, being a sincere person. While influences in social life such as growing sympathy and empathy for fellow friends, strengthen ukhuwah (solidarity), care about environmental environmental hygiene          TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//   This page is in Azerbaijani Translate to English    AfrikaansAlbanianAmharicArabicArmenianAzerbaijaniBengaliBulgarianCatalanCroatianCzechDanishDutchEnglishEstonianFinnishFrenchGermanGreekGujaratiHaitian CreoleHebrewHindiHungarianIcelandicIndonesianItalianJapaneseKannadaKazakhKhmerKoreanKurdish (Kurmanji)LaoLatvianLithuanianMalagasyMalayMalayalamMalteseMaoriMarathiMyanmar (Burmese)NepaliNorwegianPashtoPersianPolishPortuguesePunjabiRomanianRussianSamoanSimplified ChineseSlovakSlovenianSpanishSwedishTamilTeluguThaiTraditional ChineseTurkishUkrainianUrduVietnameseWelsh Always translate Azerbaijani to EnglishPRO Never translate Azerbaijani Never translate ejournal.uin-suska.ac.id